Criação e degenerescência do ensino jurídico - Reale Júnior, Miguel (Revista USP, 2014)
This is a study on the relationship between the history of law schools and inadequacy of legal studies in the country. It analyses the meaning of the first law schools in the nineteenth century as major political centers and training of bureaucracy. It deals with learning at college and not provided by college, the lack of a researching mentality and claims on the continuous insufficiency of academic training of students, which persisted until the seventies. Since then, legal teaching has witnessed an immense growth of law schools, which increased the number of students, and which has not been met with a corresponding necessary quality of professors. Furthermore, the baggage of students coming into the higher education system is deeply inconsistent, and does not allow for the proper development of the course.